A new approach to online AC impedance measurement at high frequency of PEM fuel cell stack. (27th July 2017) - Hong, Po; Xu, Liangfei; Jiang, Hongliang; Li, Jianqiu; Ouyang, Minggao
Abstract: In the PEM fuel cell system, the water management strategy is founded on the accurate water content estimation while until now it is still a large obstacle that prevents the application in the field of transportation. Focused on this problem, approaches such as the multi-mixture model have been put forward to estimate the water content but there exist some limitations. Some recent literature work shows that if they are combined with the AC impedance measurement at high frequency the estimation accuracy will be further improved. Hence, in this paper a new approach to online AC impedance measurement at high frequency is proposed by paralleling a DC/DC converter with the PEM fuel cell stack. Then the mathematical model of the stack and the converter is developed and analyzed to verify the feasibility of this method. After that, the DC/DC converter is designed and an experiment is performed on a 30 kW stack of 120-serial cells. To calculate the impedance of a cell, the cell voltage monitor is used to simultaneously measure the output current of the stack and the voltage of each cell and this device is experimentally calibrated. Under pre-scheduled experiment conditions, the variation trend of the impedance at 320 Hz of two cells in serial as a unit validates the capability of AC impedance measurement at high frequency using the DC/DC converter. Highlights: An online AC impedance measurement approach for PEM fuel cell stack is proposed based on a DC/DC converter. The average state space equations and the small signal model of the converter are derived. The experiment is conducted to validate generation of current excitation signal and weak signal extraction on a fuel cell stack. The measured AC impedance at high frequency of several cells in a 30 kW fuel cell stack is presented.